2018
DOI: 10.1111/ijfs.13771
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant activity and transcellular pathway of Asp‐Leu‐Glu‐Glu in a Caco‑2 cell monolayer

Abstract: Summary Asp‐Leu‐Glu‐Glu (DLEE) is one of the antioxidant peptides purified from Chinese dry‐cured Xuanwei ham in our previous study. In the current work, the stability in a simulated digestion system, the transportation pathway and the antioxidant ability of DLEE were further investigated in a Caco‐2 cell monolayer. In the simulated gastrointestinal digestion system, no oligopeptides were generated. In the transport trial, the inhibitors cytochalasin D increased the transport of DLEE across the Caco‐2 cell mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that molecular weight, amino acid sequence, charge characteristics, hydrogen bonding, non-enzymatic glycosylation and hydrophobicity are key factors for peptides that determine their sensitivity to peptidases and permeability through the intestinal epithelium. 23,26,27 Additionally, it is accepted that peptides with a high portion of hydrophobic amino acids, mainly aromatic and branched amino acids, could readily enter into the membrane, and they can perform free radical scavenging functions with the aid of their hydrophobicity. 28 In this study, the primary structure of the 5 peptides (TK-23, GK-19, FR-27, AR-20 and VR-16) which could be transported by the Caco-2 cells had common features: their C-terminal was rich in basic amino acids Arg (R) and Lys (K).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that molecular weight, amino acid sequence, charge characteristics, hydrogen bonding, non-enzymatic glycosylation and hydrophobicity are key factors for peptides that determine their sensitivity to peptidases and permeability through the intestinal epithelium. 23,26,27 Additionally, it is accepted that peptides with a high portion of hydrophobic amino acids, mainly aromatic and branched amino acids, could readily enter into the membrane, and they can perform free radical scavenging functions with the aid of their hydrophobicity. 28 In this study, the primary structure of the 5 peptides (TK-23, GK-19, FR-27, AR-20 and VR-16) which could be transported by the Caco-2 cells had common features: their C-terminal was rich in basic amino acids Arg (R) and Lys (K).…”
Section: Resultsmentioning
confidence: 99%
“…Wiriyaphan et al [ 26 ] demonstrated that threadfin bream-derived hydrolysate exhibited remarkable protective ability in HepG2 cells, which was related to a higher cell permeability of lower-molecular-weight peptides identified in the hydrolysate. Here, the molecular weight of DLEE was 504 Da, and the P app value of transportation across the Caco-2 cell monolayer was 3.22 × 10 −6 cm/s [ 27 ]. Thus, the intracellular capacity of DLEE may also be explained by its cell permeability in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of bioactive peptides, over the past 10 years, a high number of studies have evaluated the absorption of these peptides and the mechanisms of transport across Caco-2 cell monolayers ( Table 2 ). Thus, the absorption of intact sequences across Caco-2 cells monolayers has been demonstrated for antioxidant peptides derived from soybean protein [ 140 ], corn gluten [ 141 ], milk proteins [ 89 , 142 , 143 ], and dry-cured Xuanwei ham [ 144 ], and for antihypertensive peptides derived from lactoferrin [ 145 ], ovotransferrin [ 114 ], and ovoalbumin [ 146 ]. Similarly, this model has been used to demonstrate the efficient transport of multifunctional soybean peptide lunasin or its derived fragment RKQLQGVN by paracellular diffusion [ 96 ], and of multifunctional peptides released from lupin storage proteins by digestive enzymes [ 147 ].…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%